Production of virus-free plants of Lilium spp. from bulbs obtained in vitro and ex vitro - Chinestra, Silvia Carolina (2015)
Lilium tissue culture is used for mass propagation of elite material as well as for obtaining virus-free plants. The aim of the present study was to evaluate the effectiveness of meristem tip culture from microbulbs obtained in vitro and from bulblets obtained via scaling macropropagation – either with or without thermotherapy and chemotherapy treatments applied before meristem tip culture – to obtain virus-free Lilium spp. plants. To this end, microshoot regeneration from meristematic tips was first tested and two diagnostic techniques were compared after meristem tip culture treatment. Different alternatives were assayed in several Lilium hybrids to obtain virus-free plants. Effective virus elimination was possible using meristematic tips extracted from bulblets produced ex vitro by scaling, a procedure that has not been previously reported in Lilium. The number of virus-free plants obtained, which depended on the genotype as well as on the virus present in the original material, reached ∼100% via meristem tip culture with or without pre-thermotherapy treatment at 35 °C. Meristem tip culture produced 100% of LMoV-free plants in Lilium longiflorum ‘Snow Queen’ and LA hybrid ‘Lacorno’, also CMV-free plants in Asiatic hybrid ‘Navona’ and LA hybrid ‘Fangio’, and LSV-free plants in LA ‘Royal Respect’. The LSV infection rate decreased in Asiatic hybrid ‘Visconti’ when thermotherapy was applied ex vitro before meristem tip culture. Chemotherapy applied during in vitro bulb differentiation prior to meristem tip culture led to a complete elimination of LSV in the LO hybrid ‘Triumphator’. Ex vitro chemotherapy was ineffective in virus elimination even when applied at high concentrations.